The Effects of Financial Aid on Graduation and Labor Market Outcomes: New Evidence from Matched Education-Labor Data - Veronica Rattini (Center for Economic Studies and ifo Institute (CESifo), 2022)
Financial aid decreases the cost of acquiring additional education. By using Italian administrative and survey data on financial aid recipients and exploiting sharp discontinuities in the amount of aid received, this paper identifies the causal effect of aid generosity on college performance and labor market outcomes. The results show that students with a higher cost of college earn more credits each year than those receiving higher financial aid. This gap generates a significant difference in the overall graduation time. No differences emerge in the GPA level or in the probability of working during college. After graduation, lower-aid recipients have a similar probability of continuing to study and of working after college as higher-aid beneficiaries. However, they secure a better job match in terms of working hours and payment but also in terms of skills matching.
Keywords: H75; I22; I26; J24; 330; human capital; financial aid; labor market outcomes; regression discontinuity design